Ideal number of biopsy tumor fragments for predicting HER2 status in gastric carcinoma resection specimens - Ahn, Sangjeong (Oncotarget, 2015)
Intratumoral heterogeneity of HER2 expression is common in gastric cancers and pose a challenge for identifying patients who would benefit from anti-HER2 therapy. The aim of this study is to compare HER2 expression in biopsy and resection specimens of gastric carcinoma by immunohistochemistry (IHC) and to find the ideal number of biopsy tumor fragments that can accurately predict HER2 overexpression in the corresponding surgically resected specimen. The HER2 IHC results of 702 paired biopsy and resection specimens of gastric cancer were compared. The mean number of biopsy fragments among all cases was 4.3 (range 1–11). HER2 was positive in 130 (18.5%) endoscopic biopsies and in 102 (14.5%) gastrectomy specimens. Intratumoral heterogeneity of HER2 was found in 80 (61.5%) biopsies and 70 (68.6%) resection specimens. Out of the 70 surgical specimens with intratumoral heterogeneity, 24 (34.3%) of the corresponding biopsies were categorized as negative (positive conversion). In the 86 (12.3%) discrepant cases, negative conversion was observed in 57 (66.3%) cases and positive conversion in 29 (33.7%). The fragment numbers were significantly correlated with the discrepancy of results and positive predictability (P = 0.0315 and P = 0.0052). ROC curve analysis and positive predictability showed that 4 fragments should be obtained to minimize the differences in HER2 scores between biopsy and resection specimen. In gastric carcinomas with discrepant HER2 results between biopsy and surgical resection specimens, intratumoral heterogeneity is common with most of them showing positive conversion. To predict HER2 status precisely, at least 4 biopsy fragments containing tumor cells are required.